ACONITASE 3 is part of theANAC017 transcription factor-dependent mitochondrial dysfunction response. Issue 4 (12th May 2021) - Pascual, Jesús; Rahikainen, Moona; Angeleri, Martina; Alegre, Sara; Gossens, Richard; Shapiguzov, Alexey; Heinonen, Arttu; Trotta, Andrea; Durian, Guido; Winter, Zsófia; Sinkkonen, Jari; Kangasjärvi, Jaakko; et al.
Abstract: Mitochondria are tightly embedded within metabolic and regulatory networks that optimize plant performance in response to environmental challenges. The best-known mitochondrial retrograde signaling pathway involves stress-induced activation of the transcription factor NAC DOMAIN CONTAINING PROTEIN 17 (ANAC017), which initiates protective responses to stress-induced mitochondrial dysfunction in Arabidopsis ( Arabidopsis thaliana ). Posttranslational control of the elicited responses, however, remains poorly understood. Previous studies linked protein phosphatase 2A subunit PP2A-B'γ, a key negative regulator of stress responses, with reversible phosphorylation of ACONITASE 3 (ACO3). Here we report on ACO3 and its phosphorylation at Ser91 as key components of stress regulation that are induced by mitochondrial dysfunction. Targeted mass spectrometry-based proteomics revealed that the abundance and phosphorylation of ACO3 increased under stress, which required signaling through ANAC017. Phosphomimetic mutation at ACO3-Ser91 and accumulation of ACO3 S91D -YFP promoted the expression of genes related to mitochondrial dysfunction. Furthermore, ACO3 contributed to plant tolerance against ultraviolet B (UV-B) or antimycin A-induced mitochondrial dysfunction. These findings demonstrate that ACO3 is both a target and mediator of mitochondrial dysfunction signaling, and critical for achieving stress tolerance in Arabidopsis leaves. Abstract : ACONITASE 3 contributes to mitochondrial dysfunction signaling and stress tolerance in Arabidopsis.